Distribution of Serotypes and Antimicrobial Resistance of Streptococcus Pneumoniae in a Children’s Hospital in Nepal - Sherchand, JB; Joshi, AR; Gauchan, P; Amatya, J (Journal of Nepal Paediatric Society, 2008)
Keywords: Children; Nasopharyngeal Swab; S. pneumoniae, E-test DOI = 10.3126/jnps.v28i2.1386 J. Nepal Paediatr. Soc. Vol.28(2) 2008 p.45-48